The Widower’s Haunting Memories of His Late Wife in The Apple Tree by Daphne Du Maurier (Language Circle: Journal of Language and Literature, 2023)
The focus of analyzing the short story entitled The Apple Tree by Daphne du Maurier is on the haunting memories experienced by the husband concerning his late wife. The analysis is divided into several points; namely, the general memories of the late wife felt by the husband, a brief analysis on the husband (Buzz) and wife (Midge), the triggers of the husband’s memories, and the drastic action executed by the husband to stop the haunting memories leading to an unexpected result. The combination of methods used is to support the analysis. The textual reading is supported by close reading to dig out the important details. The contextual method in the form of borrowing suitable concepts is used to complete the textual method focusing on character and conflict. The analysis is presented using qualitative method. The result of the analysis shows that growing subjective memories of the late wife may culminate in an unreasonable hatred toward the old apple tree. Driven by uncontrolled imagination based on one-sided memories, the husband has to face unforeseen calamity alone and lonely.